2010
DOI: 10.1097/inf.0b013e3181b41506
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Lost to Rotavirus-Associated Gastroenteritis in Children and Their Parents

Abstract: We estimated the impact of rotavirus-associated gastroenteritis (RGE) on health-related quality of life of children and parents as background for economic evaluation of rotavirus vaccines. A total of 186 new cases of RGE in children <36 months old were recruited from physician and pediatric clinics and followed up for 2 weeks. Our results show that RGE impacts the health-related quality of life of children and parents adversely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 10 publications
1
53
0
1
Order By: Relevance
“…The VAS scores for the children and parents during illness were 54.8 and 73.1, respectively. The parental EQ-5D score was 0.875 during the illness episode and 0.967 at follow-up [1]. The parental VAS (78.0) and EQ-5D (0.824) scores in our study suggested that both RVGE and non-RVGE impair the HRQoL of the parents in addition to the children.…”
Section: Discussionmentioning
confidence: 50%
“…The VAS scores for the children and parents during illness were 54.8 and 73.1, respectively. The parental EQ-5D score was 0.875 during the illness episode and 0.967 at follow-up [1]. The parental VAS (78.0) and EQ-5D (0.824) scores in our study suggested that both RVGE and non-RVGE impair the HRQoL of the parents in addition to the children.…”
Section: Discussionmentioning
confidence: 50%
“…Although deaths are rare in industrialized countries, the healthcare burden of RGE-related hospitalizations and emergency department visits is substantial [6][7][8] . In addition to the healthcare burden, the impact that RGE has on the family can be considerable [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…There are 2 studies which estimated the health-related quality of life lost to RVGE or utility scores of RVGE in children. 37,51 In Brisson et al's study, caregivers evaluated health-related quality of life of their children suffering from RVGE and found out that QALY decreased by 0.0022 without differentiating between disease severity and age. 51 On the other hand, Martin et al's study showed that GPs/pediatrician were able to estimate the utility weight in children with RVGE according to disease severity and age.…”
Section: Annual Incidence Rates and Case Fatality Ratesmentioning
confidence: 99%
“…37,51 In Brisson et al's study, caregivers evaluated health-related quality of life of their children suffering from RVGE and found out that QALY decreased by 0.0022 without differentiating between disease severity and age. 51 On the other hand, Martin et al's study showed that GPs/pediatrician were able to estimate the utility weight in children with RVGE according to disease severity and age. 37 In our base-case analysis, we adopted the data set from GP estimated by Martin et al, because it fits our model better, in terms of health states after RVGE (primary care only and hospitalization) and the length of Markov cycle (1 month) taking into account the utility weight of hospitalised patients to be lower than patients who only need primary care.…”
Section: Annual Incidence Rates and Case Fatality Ratesmentioning
confidence: 99%